Trajectories of depressive symptoms after a major cardiac event - Oskar Mittag; Hanna Kampling; Erik Farin; Phillip J Tully (Health Psychology Open, 2016)
Depression is a common comorbidity in cardiac patients. This study sought to document fluctuations of depressive symptoms in the 12 months after a first major cardiac event. In all, 310 patients completed a battery of psychosocial measures including the depression subscale of the Symptom Check List-90-Revised. A total of 252 of them also completed follow-up measures at 3 and 12 months. Trajectories of depressive symptoms were classified as none, worsening symptoms, sustained remission, and persistent symptoms. Although the prevalence of depressive symptoms was consistent at each assessment, there was considerable fluctuation between symptom classes. Regression analyses were performed to identify predictors of different trajectories.